Long-Term Supplementation With Fruits and Vegetables Curbs High-Fat Diet/Obesity-Induced Changes in Body Composition and Favorably Affects Blood T Cell Phenotype in Mice. (7th June 2021) - Guo, Weimin; Wu, Dayong; Li, Lijun; Ortega, Edwin; Liu, Yankun; Ruan, Dong; Smith, Donald; Meydani, Simin
Abstract: Objectives: Obesity is associated with impaired immune function. However, impact of obesity on blood T cell profile is not well studied. The objectives of this study were to investigate the effects of high fat diet (HFD)-induced obesity and long-term fruits and vegetable (FV) consumption on body composition and blood T cell profile. Methods: This is partial report from an ongoing study. A total of 240 male C57BL/6J mice were randomly assigned to 4 groups: low fat control (LF-C) or high-fat control (HF-C) diet alone, or together with 15% of a unique mixture of FV (w/w, equivalent to 7–9 servings F&V/d for human) (LF-FV or HF-FV). The feeding will continue until 50% mortality is reached in one group. Body weight, body composition (using MRI), and blood T cell profile (using FACS) are monitored longitudinally at different time points. The results reported here are those assessed when mice were 7 months old. Results: After 7 months of feeding, mice fed HF-C gained more weight compared to those fed LF-C. Mice fed HF-FV or LF-FV diets had significantly reduced weight gain and fat mass, and higher muscle mass compared to those fed HF-C or LF-C diet, respectively. Mice fed HF-C also had significantly lower percentage of blood CD3+, CD4+, and CD8 + T cells compared with the LF-C. FV supplementation prevented HFD-induced decrease in percentage of CD3+ and CD4+ cells. Furthermore, both % CD3+ and CD4+ cells were negatively correlated with body weight ( P < 0.001) or percentage of fat mass ( P < 0.001), and positively associated with percentage of lean mass ( P < 0.001). Conclusions: Our results suggest that consuming large amounts of a unique mixture of F&V curbs HFD-induced body weight gain, reduces fat mass, and favorably affects blood T cell population. Ongoing studies will assess these analytes when mice are 16 months old, and again when one group reaches 50% mortality, and determine their correlations with functional measures of T cell response, host resistance to infection, health span, and mortality. Funding Sources: This study was supported by the U.S. Department of Agriculture – Agricultural Research Service (ARS), under Agreement No. 58–1950-4–004.